2017
DOI: 10.1049/el.2016.4333
|View full text |Cite
|
Sign up to set email alerts
|

Quad‐band BPF based on SLRs with inductive source and load coupling

Abstract: A quad-band microstrip bandpass filter (BPF) based on stub-loaded resonators (SLRs) with improved skirt selectivity is presented. A single metallic via hole in microstrip is utilised to introduce a compact inductive source-load coupling, with which two pairs of SLRs generate eight controllable transmission zeros at each side of all the quadruple passbands. As an example, a quad-band BPF with measured centre frequencies of 1.88, 2.55, 3.55 and 5.15 GHz as well as insertion losses of 1.53, 1.64, 1.79 and 2.55 dB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…1a. Due to the symmetrical structure of the resonator, the theory of odd and even modes can be used to analyze it [11][12][13].…”
Section: Analysis Of the Proposed Resonatormentioning
confidence: 99%
“…1a. Due to the symmetrical structure of the resonator, the theory of odd and even modes can be used to analyze it [11][12][13].…”
Section: Analysis Of the Proposed Resonatormentioning
confidence: 99%
“…As is well known, it is very easy to implement a dual‐band BPF rather than a quad‐band BPF. Therefore, after designing two dual‐band BPFs with different sizes, the two filters used a common input/output . The filter performance is summarized in Table .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, after designing two dual-band BPFs with different sizes, the two filters used a common input/output. [13][14][15][16] The filter performance is summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…The most direct approach is combining several resonators with common input/output ports to achieve a quad-band BPF, which suffers from a relatively large circuit area. For example, in [1], a quad-band BPF is achieved by cascading two dual-band BPFs together with a single metallic via-holed feed line. In [2], a short-end stub-loaded resonator is used to yield the third passband, and the other multi-stub-loaded resonators operate at the first, second, and fourth passband.…”
Section: Introductionmentioning
confidence: 99%
“…To settle these matters, it is vital to introduce TZs on the both sides of each passband. Source-load coupling [1], zero-degree feed lines [3], multi-paths propagation [7], meandering structure [10], and mixed electric and magnetic coupling (MEMC) configuration [11] are all capable to generate additional TZs. Besides, to the author's knowledge, very little research has been reported so far for the quad-band BPF design using QMRs under MEMC.…”
Section: Introductionmentioning
confidence: 99%